2015
DOI: 10.1149/2.0771508jes
|View full text |Cite
|
Sign up to set email alerts
|

Application of LiCoO2Particles Coated with Lithium Ortho-Oxosalt Thin Films to Sulfide-Type All-Solid-State Lithium Batteries

Abstract: Amorphous oxide thin films in the pseudobinary system Li 4 SiO 4 -Li 3 PO 4 and Li 4 GeO 4 -Li 3 PO 4 were fabricated using pulsed laser deposition (PLD) with a KrF excimer laser. The ionic conductivities of obtained thin films were 10 −8 to 10 −6 S cm −1 at room temperature. Bulk-type all-solid-state batteries using LiCoO 2 particles surface-modified with ortho-oxosalt thin films were constructed to assess the influence of oxide coatings on cell performances. Higher ion-conductive oxide thin films studied her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 30 publications
0
52
0
Order By: Relevance
“…Figure A illustrates two thin‐film batteries using Li/Li 3 PO 4 /LiCoO 2 and Li/Li 3 PS 4 /Li 3 PO 4 /LiCoO 2 , fabricated on MgO substrates. The Li 3 PO 4 layer was also introduced in the battery with the Li 3 PS 4 film electrolyte to suppress the resistive layer that generally forms at the LiCoO 2 /Li 3 PS 4 interface . The LiCoO 2 cathode (200 nm) and Li anode layers (1.5 μm) were separated by a larger square Li 3 PO 4 (~1 μm)/Li 3 PS 4 (~0.75 μm) integrated electrolyte layer or a Li 3 PO 4 (~2 μm) single electrolyte layer.…”
Section: Resultsmentioning
confidence: 99%
“…Figure A illustrates two thin‐film batteries using Li/Li 3 PO 4 /LiCoO 2 and Li/Li 3 PS 4 /Li 3 PO 4 /LiCoO 2 , fabricated on MgO substrates. The Li 3 PO 4 layer was also introduced in the battery with the Li 3 PS 4 film electrolyte to suppress the resistive layer that generally forms at the LiCoO 2 /Li 3 PS 4 interface . The LiCoO 2 cathode (200 nm) and Li anode layers (1.5 μm) were separated by a larger square Li 3 PO 4 (~1 μm)/Li 3 PS 4 (~0.75 μm) integrated electrolyte layer or a Li 3 PO 4 (~2 μm) single electrolyte layer.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, PLD can also be used to produce coatings for cathode active materials. [93] Copyright 2015, The Electrochemical Society. a,b) Adapted with permission.…”
Section: Coating Methodsmentioning
confidence: 99%
“…[95,99] Additionally, Ito et al recently generated a series of ≈45 nm oxide coatings on LCO. [93] Therein, the SSB containing Li 3 PO 4 -coated LCO exhibited smaller interfacial resistances, enhanced cycle life over 30 cycles, and improved capacities at higher current densities. One drawback of PLD is that it is a line-of-sight technique, which makes achieving homogeneous coatings rather challenging.…”
Section: Pulsed Laser Depositionmentioning
confidence: 97%
See 1 more Smart Citation
“…Consistently, the phosphates (PO 4 3− ) and sulfites (SO 3 2− ) were directly detected by time‐of‐flight secondary ion mass spectrometry measurements of the cycled LiNi 0.8 Co 0.15 Al 0.05 O 2 –75Li 2 S·25P 2 S 5 electrode . To solve this cathode interface incompatibility issue, the application of protective oxide coating layers, such as LiNbO 3 , LiNb 0.5 Ta 0.5 O 3 , Li 4 Ti 5 O 12 , Ta 2 O 5 , Al 2 O 3 , and Li 3 PO 4 between sulfide SEs and LiCoO 2 was demonstrated in previous experiments. Computational studies confirmed the improved interface stability and compatibility from the thermodynamic perspective …”
Section: Electrochemical Stability and Interface Compatibility Of Li‐mentioning
confidence: 99%